Developing of English Teaching Materials for the Communication Study Program - Nur Dahniar (ELS Journal on Interdisciplinary Studies in Humanities, 2023)
The objective of this study is to construct a communicative language that may be used to preserve the existence and to measure the quality of English for communication science students. The preparation of this design is intended so that learning English in communication sciences can run according to the initial goals and objectives. Data collection was carried out in three ways, namely: observation, questionnaires and focus group discussions (FGD). From the data obtained, there is a fact that 100% have never attended English training in communication sciences, 80% have difficulty applying communicative English, and 100% very often find things difficult in finding English vocabulary in communication sciences. The design of learning English in communication science is as follows: looking at factual conditions, learning by analysis, design, development, implementation, and evaluation, or ADDIE and the output is the implementation of communicative English in communication science for students.